Pengaruh Leverage dan Profitabilitas Terhadap Sustainable Growth Rate dengan Kebijakan Dividen Sebagai Variabel Moderasi - Yolanda, Angela; Rusmita, Sari; Hamzani, Umiaty (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
One of the important indicators that shows the company's capacity to develop sustainably without the need for additional external funding is the sustainable growth rate. With dividend policy as a moderator variable, this study tries to examine the impact of leverage and profitability on sustainable growth rate (SGR) in healthcare companies listed on the Indonesia Stock Exchange (IDX). Leverage represents the use of debt in the capital structure, while profitability is a measure of a company's capacity to generate profits which is seen as an important component in determining sustainable growth rates. The research method uses a quantitative approach with purposive sampling techniques in determining samples. A sample of 36 data, consisting of 12 companies for 3 years (2021-2023). The data analysis techniques used were descriptive and moderated regression analysis (MRA) to test the effect of moderation. This study provides implications for healthcare company management in terms of optimizing capital structure and dividend policies to achieve optimal sustainable growth. The results of the analysis show that leverage and profitability have a significant positive effect on the sustainable growth rate with significance values of 0,001 < 0,05 and 0,000 < 0,05 respectively, dividend policy does not have a significant influence on the sustainable growth rate with a significance value of 0,236 > 0,05, dividend policy has a moderation effect that weakens the relationship between leverage and sustainable growth rate with a significance value of 0,031 < 0,05, and dividend policy has a moderation effect that weakens the relationship between profitability and sustainable growth rate with a significance value of 0,000 < 0,05.